Amnioreduction with rescue cerclage at advanced cervical dilation or gestational age. (12th December 2022) - Proctor, Leslie K.; Ronzoni, Stefania; Melamed, Nir; Nevo, Ori; Cohen, Howard; Barrett, Jon
Abstract: Objective: To determine the feasibility of rescue cerclage and amnioreduction at advanced cervical dilation or gestational age. Methods: We present a retrospective case series of women who underwent rescue cerclage at either an advanced gestational age (24 + 0 to 24 + 6 weeks) or cervical dilation (≥4 cm), with a subset undergoing amnioreduction prior to cerclage placement. Results: Nine women were included and amnioreduction was performed in 7 (78%). A bi-modal distribution of obstetric outcomes was observed, with 5 (56%) women delivering ≥34 weeks gestation, 3 (33%) of which delivered at term. Two (22%) women experienced intra-operative rupture of membranes and subsequent perinatal deaths. Two (22%) women delivered extremely premature, with one resulting in infant death. Discussion: Our data show that rescue cerclage with amnioreduction may be successful at advanced gestational ages or cervical dilations, suggesting that these women should be included in prospective studies to better establish the efficacy and safety of this procedure.